Pengembangan E-Book Biologi Konstruktivistik Pada Materi Struktur dan Fungsi Sel Untuk Kelas XI SMA - St. Salmawati, St. Salmawati; Jihadi, Ahmad (Biology Teaching and Learning, 2021)
Abstract. Teaching materials in the form of constructivist biology e-books on cell structure and function material for high school grade XI are developed to be valid and practical. The e-book was developed by applying constructivist principles consisting of: (1) personalization learning, (2) reflective thinking, (3) problem solving and investigation, (4) relevance to daily-life, (5) collaborative learning, ( 6) discussion, and (7) teacher scaffolding. The e-book was developed using Microsoft Word and Scribus applications and then converted into e-books with the Flipcreator application. This type of research is Research and Development (R&D) with the ADDIE development model which has five stages, namely analysis, design, development, implementation, and evaluation. The subjects of this study were expert lecturers who tested the validity of the instruments and products developed, biology teachers and students of X MIA 2 SMAN 3 Makassar as subjects to test the practicality of the product. The results showed that the products developed were valid and practical. The validity results are in the valid category with a Va value of 4.33, the practicality test results of the teacher's response are 84.52% with the very practical category and the practicality test results of the students' responses are 95.06% with the very practical category. So, it can be concluded that the constructivist biology e-book on cell structure and function material for high school class XI developed is suitable for use in the learning process.Keywords: e-book, addie, constructivism, and cell: structure and function